2006
DOI: 10.1111/j.1365-294x.2006.03027.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection and climate change: temperature‐linked spatial and temporal trends in gene frequency in Fagus sylvatica

Abstract: Rapid increases in global temperature are likely to impose strong directional selection on many plant populations, which must therefore adapt if they are to survive. Within populations, microgeographic genetic differentiation of individuals with respect to climate suggests that some populations may adapt to changing temperatures in the short-term through rapid changes in gene frequency. We used a genome scan to identify temperature-related adaptive differentiation of individuals of the tree species Fagus sylva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
227
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(244 citation statements)
references
References 61 publications
8
227
0
2
Order By: Relevance
“…In Engelmann spruce (Picea engelmannii), Mitton et al (1989) found association between genotypes at the phosphoglucomutase (PGM) isozyme locus and drought stress in sub-populations separated by few tens of metres; the same research group found associations between isozyme genotypes at the glycerate dehydrogenase (GLY) locus and stomatal size, on the one side, and soil moisture, on the other side, in pinyon pine (Pinus edulis) over distances in the order of hundreds of metres (Cobb et al 1994;Mitton et al 1998); Kelly et al (2003) found that a single birch (Betula pendula) stand could be sorted into genetic groups associated to temperature at seedling establishment, according to 358 amplified fragment length polymorphism (AFLP) markers. In a similar study, in European beech (Fagus sylvatica), Jump et al (2006) found one AFLP marker (out of 254 screened) associated with spatial and temporal variations in temperature at seedling establishment and differentiation between sub-populations less than 3 km apart; in the same species, Pluess and Weber (2012) found three AFLPs (among 517) associated with moisture across populations separated by only 0.5 km, and Csilléry et al (2014) identified contrasted signatures of selection for multi-locus single nucleotide polymorphism (SNP) combinations in a set of 546 SNPs from 53 climate response genes, in sub-populations sampled over an elevation gradient spanning less than 5 km. A similar study in Norway spruce (Scalfi et al 2014) found two SNP loci (out of 384) associated with elevation; Brousseau et al (2013) found extensive divergence for functional traits in contiguous subpopulations of tropical Eperua falcata and Eperua grandiflora, interspersed and located on seasonally flooded or vertically drained soils; in the same populations of E. falcata, Audigeos et al (2013) found that genotypes and alleles were associated to soil type at eight out of 88 SNPs from seven candidate genes and for three of the same genes at the haplotype level.…”
Section: Microgeographic Variation In Forest Trees: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…In Engelmann spruce (Picea engelmannii), Mitton et al (1989) found association between genotypes at the phosphoglucomutase (PGM) isozyme locus and drought stress in sub-populations separated by few tens of metres; the same research group found associations between isozyme genotypes at the glycerate dehydrogenase (GLY) locus and stomatal size, on the one side, and soil moisture, on the other side, in pinyon pine (Pinus edulis) over distances in the order of hundreds of metres (Cobb et al 1994;Mitton et al 1998); Kelly et al (2003) found that a single birch (Betula pendula) stand could be sorted into genetic groups associated to temperature at seedling establishment, according to 358 amplified fragment length polymorphism (AFLP) markers. In a similar study, in European beech (Fagus sylvatica), Jump et al (2006) found one AFLP marker (out of 254 screened) associated with spatial and temporal variations in temperature at seedling establishment and differentiation between sub-populations less than 3 km apart; in the same species, Pluess and Weber (2012) found three AFLPs (among 517) associated with moisture across populations separated by only 0.5 km, and Csilléry et al (2014) identified contrasted signatures of selection for multi-locus single nucleotide polymorphism (SNP) combinations in a set of 546 SNPs from 53 climate response genes, in sub-populations sampled over an elevation gradient spanning less than 5 km. A similar study in Norway spruce (Scalfi et al 2014) found two SNP loci (out of 384) associated with elevation; Brousseau et al (2013) found extensive divergence for functional traits in contiguous subpopulations of tropical Eperua falcata and Eperua grandiflora, interspersed and located on seasonally flooded or vertically drained soils; in the same populations of E. falcata, Audigeos et al (2013) found that genotypes and alleles were associated to soil type at eight out of 88 SNPs from seven candidate genes and for three of the same genes at the haplotype level.…”
Section: Microgeographic Variation In Forest Trees: State Of the Artmentioning
confidence: 99%
“…These factors can seriously limit our ability to detect selection; however, if we are able to setup studies taking into account temporal data (e.g. Jump et al 2006) and multiple life stages (e.g. Alía et al 2014), the breakdown of effects of selection into Csilléry et al (2014) temporal and ontogenetic components should be possible.…”
Section: How Much Selection?mentioning
confidence: 99%
“…Some individual trees might be acclimating in situ to new climatic conditions (e.g. Jump et al, 2006b) that could render them more competitive and/or profit from the decline or death of other trees in the stand. Black pine populations in southern Spain have lower intra-population genetic diversity (Martín-Albertos and Gonzalez-Martínez, 2000) and are genetically isolated from populations further north (Afzal-Rafii and Dodd, 2007), supporting the higher similarity between individual tree growth patterns in SCA.…”
Section: Radial Growth Trends and Their Climatic Driversmentioning
confidence: 99%
“…Subtropical China is marked by clear latitudinal temperature (cooler in the north) and longitudinal precipitation (wetter in the east) gradients. These environmental gradients can impose strong selective pressure on plant populations, driving local adaptation (Jump et al, 2006;Eveno et al, 2008). Morphological variation on leaves and cupules of C. fargesii are observed across its whole distribution range (Huang and Chang, 1998), and a high level of genetic diversity of four populations of C. fargesii in Fujian province has been detected using six genomic microsatellite molecular markers (Xu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%